Coping with chronic musculoskeletal pain in Portugal and in the United States: A cross-cultural study - Valente, Maria Alexandra Ferreira (2013)
Objective. The aim of this study was to examine the associations between coping and adjustment to chronic pain in a sample of patients from Portugal and to discuss the findings with respect to published findings from two studies using patients from the United States. Design. Two brief measures of pain coping were translated and administered with measures of physical and psychological functioning to a sample of Portuguese patients. Analyses examined the associations among the study variables and compared the results with published data from two patient samples from the United States. Participants. One hundred seventeen individuals with chronic musculoskeletal pain. Outcome Measures. Portuguese translations of brief versions of the Coping Strategies Questionnaire and Chronic Pain Coping Inventory and criterion measures of pain intensity, pain interference, and depression. Results. Statistically significant positive associations were found between measures of patient dysfunction and catastrophizing, praying/hoping, guarding, asking for assistance, and support seeking; and negative associations were found between the criterion measures and ignoring sensations, coping self-statements, and increasing behavioral activities. Mean differences between the Portuguese and US samples in the coping scales were found for nine of the 15 coping scales. Conclusions. The results support the reliability and validity of the translated Coping Strategies Questionnaire and Chronic Pain Coping Inventory and also indicate a number of similarities, but also some interesting differences, in the findings from the Portuguese vs US samples, suggesting that there may be cultural differences in how people cope with pain.